(untitled) (Homoeopathy for All, 2023)
lipids & lipoproteins in the blood has become a common clinical problem of the century which has turned out to be a challenge to the physician. Maintaining healthy Cardio vascular system is a significant part of maintaining good quality of life. Cholesterol plays a vital role in getting cardiac diseases with more prevalence. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this Cholesterol disorder.